Double-pass EDFA with built-in variable optical Bragg grating - Jamaludin M.Z.; Bakar A.A.A.; Abdullah F.; Rahman F.A.; Mahdi M.A.; Abdullah M.K. (2023)
A double-pass erbium-doped fiber amplifier (EDFA) with built-in Variable Optical Bragg Grating (VOBG) is presented to provide a gain as high as 49.06 dB with a noise figure of 5.12 dB. The system provides a gain improvement of as much as 12.5 dB from the conventional double-pass system (without filter). This is all achieved with EDF length of 12 m and pump power of 100 mW. 2005 IEEE.